The Last Place in the World - Copyright Protection for Computer Software in New Zealand - Cash, B (Victoria University of Wellington Law Review, 1997)
Computer technology - whether it is hardware, software or the internet - is the headache that just won’t go away for anyone grappling with the law of intellectual property. With the Copyright Act 1994, the New Zealand legislature attempted to meet some of the challenges but it largely avoided the issue, passing the headache onto the judiciary should any tricky issues arise. One such issue is copyright protection for computer programs. The Copyright Act 1994 makes it clear that computer programs are protected as a literary work but how far does that protection extend (or how far do we carry the fiction that a computer program is literary work)? This article attempts to second guess what level of protection our courts might provide. It argues that New Zealand has shown a willingness to protect functional items and would protect the "look and feel" of a program, providing a level of protection which courts in the United States have considered undesirable.